Immobilization of á-amylase (ban) for sago starch hydrolysis - Khairil Nazuan, Mohd (2006)
α-Amylase produced from Baccilus Amyliquifaciens (termamyl) was immobilized by entrapment in calcium alginate gel capsules and it was used repeatedly in batch processes of starch hydrolysis. The degree of starch degradation and operational stability of the immobilized system were increased by tailoring the characteristics of the capsules. Capsules prepared from 2% (w/v) sodium alginate and 5% (w/v) CaCl2 were suitable for up to 20 repeated uses, losing only 30% of their initial efficiency. These alginate/silica capsules carrying α-Amylase retained 90% of their initial efficiency after 20 starch hydrolysis batches and released more than 10,700 mg of reducing sugars during a processing period of 160 h.